KONSTRUKSI MAKNA KHURUJ FI SABILILLAH BAGI ANGGOTA JAMAAH TABLIGH DI KOTA PEKANBARU - Iman, Mhd. Afdhalul; Wirman, Welly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The existence of various Islamic groups in the community that developed into a phenomenon that continues to grow today. One group was the Tablighi Jamaat. In appearance, the group Tablighi Jamaat has characteristics that resemble groups of Salafi-Wahabi. But in fact, these groups have some differences. One difference is khuruj fi sabilillah. Khuruj fi sabilillah is taking the time path of Allah by using treasure and myself, moving from one place to another to establish a friendship in the framework of propaganda and sermons, from mosque to mosque worldwide. Da'wah movement is actually not a local movement, but the movement of international propaganda which originated in India in 1926 by Maulana Muhammad Ilyas and continues to expand to all corners of the world to date. The development of the missionary movement is evidenced by the many mosques into their activities. This study aims to determine the motive, the meaning and experience of members of Tablighi Jamaat communication in implementing the khuruj sabilillah in Pekanbaru city. This study uses qualitative research with phenomenological approach. Subjects consisted of five members of the Tablighi Jamaat in the city of Pekanbaru selected by the snowball technique. The study used data collection techniques in-depth interviews, participant observation, and documentation study. To achieve the validity of the data in this study, the authors used the extension of participation and triangulation. The results showed first, the motive member of Tablighi Jamaat implement khuruj fi sabilillah in Pekanbaru City consists of a motive for (Because motive) that is orders of Allah and worried to see the condition of the people. While the motive of hope (in order to motive) that improve and encourage people to practice religion. Second, the meaning of a given member of Tablighi Jamaat against him that is jihad fi sabilillah, sacrifice for the religion, Historian life and struggle of the prophet. Third, the communication experience categorized into two communication experience fun in the form of a good reception from family, support from fellow Tablighi Jamaat, a positive response from the public and community leaders. and communication experience unpleasant form of a prohibition of family, satire and scorn of the community and community objections.Keywords:Jamaah Tabligh, symbolic interaction, Phenomenon, Khuruj fi sabilillah